Andarilhos de Estrada e Trecheiros: percepções sobre a condição de vida, cidadania e acesso à Seguridade Social - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
The continuous roaming of nomads and wanderers stems from personal, social and structural problems influenced by capitalism and globalization, conjugated in modernity. The lives of hikers and trecheiros are marked by social ills, the physical and psychological suffering of everyday life on the roads and the absence of the State. The purpose of the first article is to identify the characteristics present in wandering and nomadism; and to present, in the form of an experience report, the statistical data and the main moments of the work developed during the Vidas na Estrada Project: walkers and trecheiros. The proposed methodological paths are the bibliographic review, documental research, and field work, presenting data from two approaches that are part of Vidas na Estrada project. It was concluded that the living conditions of these road walkers present traits which, when combined, project a low life expectancy on the subjects. It was empirically verified, with a significant sample of nomads and wanderers, some convictions that already exist in the academic environment, as well as data not previously mentioned in the scientific literature regarding contemporary wandering and nomadism. A wonderer’s life is perceived as the last alternative of a life permeated by suffering and disillusionment, in which misery manifests itself in a material and existential way. On the shoulders of Brazilian highways, it is possible to see people walking aimlessly, barely carrying anything, in bags, wheelbarrows or on the back of bicycles. They are the road walkers, practically invisible and socially excluded. The exclusion experienced by these wanderers is completely at odds with the Principle of Human Dignity, fundamental to the Federal Constitution, and foundation of citizenship and public policies. The aim of this article is to carry out a systematic review of the literature available in virtual repositories of journals, theses, and dissertations to establish the state of knowledge regarding publications that associate wandering and nomadism with access to public policies in Social Assistance. The methodology used was the State of Knowledge. Preliminarily, 35 works were found and, after selection based on the objectives of the study, 04 articles and 01 thesis remained that were analyzed. From reading the material, it was possible to conclude that the services offered by Social Policy provided by the State do not reach the road wanderers, due exactly to their wandering condition. There are no studies that focus on the citizenship of wanderers, therefore there is a need for more specific studies that address which modus operandi can be implemented so that assistance services reach the Road Walkers.
Keywords: Andarilhos de Estrada; Trecheiros; Direitos Sociais; Cidadania; Road Wanderers; Trecheiros; Social Rights; Citizenship; CNPQ::CIENCIAS SOCIAIS APLICADAS